Implementation Of Digital Learning To Improve Students' Learning Activity In The Subject Of Al-Qur'an Hadith - Maisarah, Maisarah; Salsabilla, Putri; Dewi, Kurnia (ISTIFHAM, 2024)
This study aims to examine the application of digital learning in the Al-Qur'an Hadith subject at MAN 1 West Aceh using the Classroom Action Research (CAR) method of the Kemmis-Taggart model. The results of the study indicate that digital learning is learning that uses digital technology to convey material to students, which can be done by using devices such as computers, tablets, and smartphones, using online learning platforms, using educational applications using the internet to search for sources of information and present learning materials contextually and delivering audio-visual materials in the form of text, graphics, animations, or videos. Success of Digital Learning Student scores (blue) tends to be higher than scores (green), especially in the aspects of Average, Max, and Mean, indicating the effectiveness of the application of digital learning on student activity in the Al-Qur'an Hadith subject. In terms of Data Diversity, the Standard Deviation (Std) and Variance (Var) have small values, indicating that student learning outcomes are quite consistent, with little deviation between students. Meanwhile, in terms of value distribution, the maximum student value is very high, almost reaching 100%, indicating that there are students who are very active and involved. The value mode is also significant, indicating a consistent pattern of success in the majority of students and in terms of Score Gap and score values (green) have much smaller values than the values​ (blue) on each indicator. This shows that the value as a representation of final achievement is more prominent than the initial score or other indicators.